Radiologic and Histopathologic Evaluation of Canine Artery Occlusion after Collagen-Coated Platinum Microcoil Delivery - Tamatani, Shinichi; Ozawa, Tsunenori; Minakawa, Takashi; Takeuchi, Shigekazu; Koike, Tetsuo; Tanaka, Ryuichi (American Journal of Neuroradiology, 1999)
BACKGROUND AND PURPOSE: Platinum coil embolization is one of the significant advances in interventional neuroradiologic techniques that has been introduced this decade. Our purpose was to evaluate the angiographic and histologic effects of collagen-coated platinum microcoil delivery in the canine artery.METHODS: We embolized the bilateral internal maxillary arteries of 18 dogs; one uncoated and one collagen-primed coil was used in each dog. We evaluated all coils by angiography, macroscopy, and scanning electron microscopy within 30 minutes of embolization. We then studied a proportional number of coated and collagen-primed coils at either 1 or 3 days, or 1, 2, 3, 4, 8, 12, or 16 weeks postoperatively.RESULTS: Six (33%) of 18 arteries embolized with uncoated coils were occluded 30 minutes after delivery, whereas 11 (61%) of 18 arteries treated with collagen-primed coils were occluded within 30 minutes of embolization. Late occlusion (3 weeks after embolization) occurred in 2 (25%) of 8 arteries embolized with untreated coils, and 6 (75%) of 8 arteries embolized with collagen-primed coils. We calculated differences in late occlusion rates by the χ2 (chi-square) test, and found these differences were significant (P=.04). Histologic findings of arteries embolized with unprimed coils revealed endothelial cell growth was limited to the organized thrombi 4 weeks after coil delivery. In contrast, endothelial cells grew directly on the collagen-primed coils 3 days postoperatively, and coils were completely covered by endothelial cells within 2 weeks. We found an organized thrombus in the inner space of coils in angiographically occluded arteries, a finding that was not evident in angiographically patent arteries.CONCLUSION: Collagen-coated platinum coils can produce rapid and stable occlusion of embolized vessels.